LONG-ACTING DRUGS AND FORMULATIONS FOR THE TREATMENT AND PREVENTION OF HIV - Flexner, Charles (Int J Antimicrob Agents, 2020)
Long acting and extended-release formulations represent one of the most important approaches to improving the treatment and prevention of chronic HIV infection. Long acting small molecules and monoclonal antibodies have demonstrated potent anti-HIV activity in early and late stage clinical trials. Strategies to manage toxicities and falling drug concentrations after missed doses, as well as primary and secondary resistance to current drugs and monoclonal antibodies are important considerations. Long-acting injectable nanoformulations of the integrase inhibitor carbotegravir and the nonnucleoside reverse transcriptase inhibitor rilpivirine were safe, well tolerated, and efficacious in large randomized Phase 3 studies. Regulatory approval for this 2-drug combination for HIV maintenance therapy was granted in Canada in 2020 and is expected in the U.S. during 2021. 4′-ethynyl-2-fluoro-2′-deoxyadenosine (islatravir) is a novel nucleoside reverse transcriptase inhibitor in clinical development as a long acting oral drug and as a long-acting subcutaneous polymer implant. GS-6207 is a novel HIV capsid inhibitor that is injected subcutaneously every 3 months. Broadly neutralizing monoclonal antibodies have potent antiviral activity in early human trials; however, there is substantial baseline resistance, and rapid development of resistance to these antibodies if used as monotherapy. Limitations of these antiretroviral approaches include the management of toxicities, and prevention of drug resistance when these drugs are discontinued and drug concentrations are slowly reduced over time. These approaches appear to be especially attractive for patients complaining of pill fatigue, and for those experiencing HIV-associated stigma. As these formulations are shown to be safe, well-tolerated, and economical, they are likely to gain broader appeal.